An organizational perspective on human-centered design for inclusive innovations - Muller, Anna; Steinke, Jonathan; Dorado, Hugo; Keller, Salome; Jimenez, Daniel; Berta Ortiz-Crespo; Schumann, Charlotte (2023)
1. CONTEXT Human-Centered Design (HCD) is gaining attention in international research and development and is increasingly integrated into the CGIAR portfolio, particularly by digital innovation projects. HCD is a creative approach to problem solving that places the target group’s needs, context, pain points, and aspirations at the heart of the innovation process. It assumes that a needs-centered, iterative and open-ended process results in more inclusive innovations with greater uptake and impact, compared to more linear research processes that test preconceived solutions. HCD in the CGIAR has been applied, for example, to design digital advisory systems accessible for low literate farmers with limited access to phones (Ortiz-Crespo et al., 2021). Discussions arise how HCD can be brought more systematically into inclusive innovation processes within CGIAR. With the implementation of HCD in CGIAR research-based innovation projects, particular challenges and tensions arise that influence the outcome of an HCD process. Particularly interesting is how CGIAR works with HCD as an organization and how research-based innovation processes are organized within programs and teams. It is not a new notion that the outcome of process-based innovations (as HCD for the CGIAR) depends on internal structures and enabling conditions. But a systematic, critical reflection guided towards understanding internal factors that enable or hinder the implementation and successful impact of HCD within CGIAR – and potentially similar organizations - has not happened so far. 2. OBJECTIVE This short communication presents the results of research into the organizational patterns that enable or challenge the effective implementation of HCD as a process towards more inclusive innovations within the CGIAR. It also builds a more comprehensive idea on how a more HCD mature organizational context could look like and derives recommendations for further organizational development and change. 3. METHODS We focus our organizational research on CGIAR as an exemplary organization of the AR4D world. For understanding the current use and impact of HCD at the organizational level, we adapted a framework developed to assess organizational UX maturity (Nielsen Norman Group, 2023a). We developed a survey that generated 24 responses. To get a more nuanced understanding of enablers and challenges for effective HCD implementation in the context of inclusive innovations, and to build a common idea about a more HCD mature organizational scenario, we consulted 5 HCD experts from inside and outside the CGIAR. 4. RESULTS AND CONCLUSIONS The HCD maturity that we assessed with the survey is stage 2. In organizations of this type, HCD implementation is limited. We can also see from the results, that the maturity in the areas of culture is much higher than in strategy, processes, and outcomes. This implies that there is a general openness and interest in HCD, but there HCD is not strategically implemented, there is little budget, human-centered research and design processes are not well established, and outcomes of HCD are poor and rarely documented and measured. Experts see as the main enablers for effective HCD implementation in CGIAR a) external drivers, as the digital transformation trend and donor interest; b) a mindset based on research curiosity and openness; c) the existing familiarity with social science and qualitative methods; and d) first established processes. Challenges arise around a) donor pressure to deliver outputs; b) a prevailing technological determinism; c) a general misconception of what HCD is. In a more HCD mature CGIAR, experts see researchers and designers working together in cross-functional teams, valuing each other’s contribution and continuously interacting with users. We conclude by discussing concrete steps recommendable for this stage of HCD maturity and we embed our results in a broader discussion around technological determinism and research paradigms.